Pengaruh Penempatan Karyawan terhadap Kepuasan Kerja Karyawan pada PT. POC Jambi - Muhtadin, M. Al; Wahyudi, M. Agus; Hutapea, Ronald (https://jurnal.binamandiri.ac.id/, 2021)
This study aims to understand the placement of employees in job satisfaction at PT. POC Jambi and to find out how much influence this variable partially and which factors are the most dominant in influencing job satisfaction at PT. PO. Data analysis uses simple linear regression to test whether employee placement affects job satisfaction at PT. PO. The data was processed with the help of the SPSS computer program. Based on the t-test, it was found that the placement of employees increased job satisfaction by 28.4%.